16 RAM cannula versus Infant Flow Driver systems for post-extubation non-invasive ventilation support in extremely preterm infants - A retrospective cohort study. (21st October 2022) - Kumar, Manoj; Keil, Eric
Abstract: Background: Non-invasive ventilation (NIV) delivered by RAM cannula is being used for post-extubation support of preterm infants in some centers for its potential benefits of ease of setup and less nasal trauma. Objectives: To assess characteristics and clinical outcomes for infants extubated to NIV support delivered via RAM cannula, as compared to those extubated to Vyaire Infant Flow Driver (IFD) systems. Design/Methods: Retrospective cohort study. All infants born at 25 to 27 + 6 weeks of gestation during a 3-year period (2016-2018) and admitted to a regional Level-3 NICU, were eligible if: 1) they were ventilated for RDS within 48 hours of birth, and 2) extubated to NIV support using RAM cannula or IFD systems (using Viasys or Fabian TM devices). Primary outcome was the failure of the primary mode of NIV support within the first 72 hours post-extubation (defined as need for reintubation or change of initial NIV mode to prevent reintubation). We adjusted for antenatal steroid use and delivery route. Data was stratified for gestational age (GA) <26 wks/>=26 wks. Sensitivity analysis were performed on additional parameters, e.g., inborn status, duration of initial ventilation restricted to <4 days. Logistic and linear regression models were built for the categorical and continuous outcomes. Results: 150 infants were enrolled, RAM cannula (n = 62) and IFD devices (n = 88). The majority of patients in both groups were on conventional ventilation, received one dose of surfactant, and were on FiO2 <0.3 prior to extubation. RAM cannula group had significantly longer duration of intubation prior to first extubation (median duration 99 hrs vs 19 hrs). There was no difference in the primary outcome between the groups [(RAM 51.6% and IFD 45.5%; adjOR 1.25(95% CIs: 0.65 – 2.4)]. However, RAM cannula group had higher rates of reintubation within <=7 days after extubation (89.5% vs 68.5%; adjOR 3.87(95% CIs: 1.18, 12.73), p-value=0.026] and higher incidence of IVH [62.9% vs 38.6%; 2.77(95% CIs: 1.39, 5.53), p-value 0.004], with lesser infants weaned to room air prior to discharge [58.1% vs 76.1.6%; adjOR 0.42(95% CIs: 0.21, 0.85), p-value 0.016]. In the stratified analyses by GA, these differences were noted to be restricted to those born at >=26 weeks, with an additional risk for increased BPD36 (adjORs 2.76 (95% CIs: 1.16, 6.57), p-value 0.022] associated with the RAM cannula use in this stratum. Conclusion: Post-extubation NIV support via RAM cannula, as compared to IFD systems, was associated with higher rates of reintubation in <=7 days, IVH, with a greater number of infants discharged home on supplemental oxygen.